On human capital formation with exit options: comment and new results - Panu Poutvaara (Institute for the Study of Labor (IZA), 2005)
Katz and Rapoport (2005) conclude that with linear production technology and the possibility of unilateral migration, region-specific shocks may increase the average level of education. Previously, Poutvaara (2000) derived a corresponding result with Cobb-Douglas technology and migration which may go in both directions. This paper shows that the exit option may reduce human capital formation with a quadratic production technology.
Keywords: F22; J24; I21; 330; human capital formation; migration; economic volatility; Humankapital; Mobilität; Bildungsinvestition; Produktionsfunktion; Migrationstheorie; Theorie